NF-YB family transcription factors in Arabidopsis: Structure, phylogeny, and expression analysis in biotic and abiotic stresses - Bhattacharjee, Bipasha; Hallan, Vipin (Frontiers in Microbiology, 2023)
Nuclear factor-Y (NF-Y) transcription factors (TFs) are conserved heterotrimeric complexes present and widespread across eukaryotes. Three main subunits make up the structural and functional aspect of the NF-Y protein: NF-YA, NF-YB and NF-YC, which bind to the conserved CCAAT- box of the promoter region of specific genes, while also interacting with each other, thereby forming myriad combinations. The NF-YB TFs are expressed differentially in various tissues or plant development stages, likely impacting many of the cellular processes constitutively and under stress conditions. In this study, 10 members of NF-YB family from Arabidopsis thaliana were identified and expression profiles were mined from microarray data under different biotic and abiotic conditions, revealing key insights into the involvement of this class of proteins in the cellular and biological processes in Arabidopsis. In silico expression analysis inferred distinct patterns of expression in various tissues, with respect to different treatments such as drought, cold and heat stress as well as bacterial, fungal, and viral stress, indicating their likelihood of having an expansive range of regulatory functions under native and stressed conditions; while quantitative real-time PCR (qRT-PCR) based expression analysis revealed that these TFs get real-time- modulated in a stress dependent manner. Moreover, analysis of cis-acting regulatory elements (CAREs) indicated the presence of majorly abiotic and biotic stress-related transcription factor binding sites (TFBs), which provided insight into the involvement of this class of proteins in an expansive range of regulatory functions under native and stressed conditions. This study, consequently, provides an understanding of the AtNF-YB family of TFs in their regulation and participation in various morphogenetic and defense- related pathways and can provide insights for development of transgenic plants for trait dependent studies.